Essays on the Portuguese economy: the era of financialisation - Barradas, Ricardo Pereira (2016)
This PhD thesis aims to assess the financialisation process in Portugal since the early 1980s and a particular dimension of the respective process in the European Union countries since the mid-1990s, through the compilation of four inter-related Essays. The broad and complex concept of financialisation tends to offer a negative perspective on the impact of growth of finance in the economy, contrary to the predictions of mainstream economics that considers the growth of finance as a general positive phenomenon. In that sense, the emergence of financialisation in Portugal is contextualised in an historical, economic and international perspective in the first Essay. Based on the analysis of several indicators, this Essay concludes that the Portuguese economy exhibits symptoms of financialisation that put in evidence its structural weaknesses and played an important role on the recent sovereign debt crisis. The second Essay aims to address empirically the relationship between financialisation and the Portuguese real investment through a time series econometric analysis. Financialisation, on the one hand, leads to a rise of financial investments by non-financial corporations, which deviates funds from real investments (“crowding out” effect). On the other hand, strong pressures around the intensification of financial payments restrain funds available for real investments. This Essay concludes that the financialisation process has hampered the Portuguese real investment, mainly through the channel linked with financial payments. The empirical analysis of the second Essay is extended to the European Union countries in the third Essay using a panel data econometric analysis. This Essay concludes that the financialisation process has also damaged real investment in European Union countries, mainly through the financial payments channel. The Essay is also able to identify that the financialisation process causes a higher slowdown in real investment in the more financialised countries, which represents an important conclusion for a less financialised economy like Portugal. The fourth Essay aims to assess empirically the relationship between financialisation and the Portuguese labour income share, conducting a time series econometric analysis. The financialisation process tends to increase the inequality on functional income distribution, visible in the growing importance of profit share in viidetriment of labour income share, which occurs through three channels: the change in the sectorial composition of the economy (due to the increase of the weight of financial activity and the decrease of government activity), the shareholder value philosophy and the weakening of trade unions. The Essay finds evidence that the financialisation process affected the evolution of the Portuguese labour income share, namely trough changes in government activity and in trade union density. Overall, this PhD thesis offers further evidence that the financialisation process also affects negatively and from different prisms the smaller, less developed and more peripheral economies, such as Portugal.